Pengaruh Disiplin Kerja, Work-Life Balance Dan Kreativitas Terhadap Produktivitas Karyawan PT. Makhtab Madani Akbar - Fadli Saputra; Roni Fadli (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the effect of work discipline, work-life balance, and creativity on employee productivity at PT. Makhtab Madani Akbar. This research uses a quantitative method with an associative approach. The population of this study consists of all 50 employees of PT. Makhtab Madani Akbar, using a saturated sampling technique in which all population members are used as respondents. Data were collected through questionnaires, observations, and literature studies. The data analysis techniques include instrument testing, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing using the t-test and f-test. The of study indicate that partially (t-test), the significance values of work discipline, work-life balance, and creativity are less than 0.05, meaning that these variables have a positive and significant effect on employee productivity. Simultaneously (F-test), the significance value is also less than 0.05,indicating that work discipline, work-life balance, an creativity have a significant effect on employee productivity at PT. Makhtab Madani Akbar. These findings indicate that improving employee productivity can be achieved through consistent work discipline, proper management of work-life balance, and providing support and opportunities for employee creativity.